1993
DOI: 10.1210/en.133.2.482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rat uterine neuromedin U receptor

Abstract: Neuromedin U (NmU) is a novel peptide that potently contracts smooth muscle, including rat uterus in vitro. No receptors have so far been demonstrated in any tissue. We have characterized the receptor for NmU in rat uterine membrane preparations. The binding of [125I] rat NmU was saturable, specific, reversible, and time, temperature, and pH dependent. The nonhydrolysable analog of GTP, GTP-gamma-S, reduced binding in a dose-dependent manner, suggesting that the binding site is coupled to a G-protein. Scatchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…The latter peptide produced similar EC 50 values to those reported previously (16 Ϯ 5 nM (22); 46 Ϯ 8 nM (38)). In addition, the IC 50 value obtained for inhibition of monoradioiodinated rat NmU binding to rat uterine membrane preparations (60 nM) was of a similar magnitude to that previously reported (35)). However, in the absence of suitable NmU receptor antagonists, it is not possible to state unequivocally whether both peptides activate or indeed bind to the same receptor.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The latter peptide produced similar EC 50 values to those reported previously (16 Ϯ 5 nM (22); 46 Ϯ 8 nM (38)). In addition, the IC 50 value obtained for inhibition of monoradioiodinated rat NmU binding to rat uterine membrane preparations (60 nM) was of a similar magnitude to that previously reported (35)). However, in the absence of suitable NmU receptor antagonists, it is not possible to state unequivocally whether both peptides activate or indeed bind to the same receptor.…”
Section: Discussionsupporting
confidence: 88%
“…Uterus membranes were prepared by differential centrifugation, as described previously (35). Membranes were resuspended in ice-cold HEPES (50 mM) buffer (pH 7.6) containing soybean trypsin inhibitor (10 g/ml), pepstatin (0.5 g/ml), leupeptin (0.5 g/ml), antipain (0.5 g/ml), benzamidine (0.1 g/ml), aprotinin (30 g/ml), and bacitracin (0.1 g/ml) to a final concentration of approximately 10 mg of protein/ml and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analyses for FM-3 mRNA expression levels using quantitative reverse transcription-polymerase chain reaction (RT-PCR) indicated that FM-3 mRNA was expressed highly in the small intestine and lung of rats, but only very low levels were detected in the uterus. Nonetheless neuromedin U has reportedly shown very strong contractile activity (1,2), and numerous binding sites have been detected in rat uterine tissue (11,12). We considered that this discrepancy might be due to the existence of an unknown receptor subtype for neuromedin U in the rat uterus.…”
mentioning
confidence: 95%